Antimicrobial Sensitivity Pattern of the isolated Uropathogens at a Teaching Hospital (Journal of Science Foundation, 2020)
Background: Urinary tract infection is the most common infection occurs in both male and female.Objective: This study was aimed to identify the uropathogens and their antimicrobial sensitivity pattern.Methodology: This study was carried out in the Department of Microbiology at Dhaka National Medical College & Hospital, Dhaka from January 2018 to December 2018.Result: A total of 1686 samples of urine were collected from suspected cases of urinary tract infections from Dhaka National Medical College & Hospital. Among them, 292 (17.32%) specimens showed significant bacterial growth. The most common uropathogens isolated were Escherichia coli.Conclusion: In conclusion Gram negative bacteria is the commonest uropathogens isolated.Journal of Science Foundation July 2019;17(2):42-45